Task- and Rest-based Functional Brain Connectivity in Food-related Reward Processes among Healthy Adolescents. (1st March 2021) - Charroud, Céline; Poulen, Gaëtan; Sanrey, Emily; Menjot de Champfleur, Nicolas; Deverdun, Jérémy; Coubes, Philippe; Le Bars, Emmanuelle
Highlights: Adolescents underwent two MRI sessions: pre-lunch (hunger) and post-lunch (satiety). Increased connectivity in the right posterior insula/accumbens nucleus while hungry. Right lateralization involves exteroceptive signals with stimulus salience in the task. Left lateralization might involve salient interoceptive signal during resting-state. Orbitofrontal cortices are involved in the suppression of the affective information. Abstract: It is known that the nucleus accumbens, orbitofrontal cortex and insula play a role in food-related reward processes. Although their interconnectedness would be an ideal topic for understanding food intake mechanisms, it nevertheless remains unclear especially in adolescent. Therefore, this study aims to investigate the effect of hunger on functional connectivity in healthy adolescents using task- and rest-based imaging. Fifteen participants underwent two MRI sessions, pre-lunch (hunger) and post-lunch (satiety), including food cue task and resting-state. During task- and rest-based imaging, functional connectivity was greater when hungry as opposed to satiated between the right posterior insula/nucleus accumbens, suggesting involvement of salient interoceptive stimuli signals. During task-based imaging, an increase was observed in functional connectivity when hungry as opposed to satiated between the medial and lateral orbitofrontal cortex which contributes to the perception of food deprivation as a frustration. A decrease was identified when hungry as opposed to satiated in functional connectivity in the right anterior orbitofrontal/accumbens and posterior insula/medial orbitofrontal cortices reflecting suppression of the affective and sensorial information. Conversely, functional connectivity was increased during aversive stimuli between the right medial orbitofrontal cortex and right posterior insula when hungry as opposed to satiated. This suggests that the value of valence could occur in the shift in connectivity between these two regions. In addition, during rest-based imaging, a left-sided lateralization was reported (accumbens/lateral orbitofrontal and accumbens/posterior insula) when hungry as opposed to satiated which may represent changes in internal state due to focus on the benefit of an upcoming meal.